The influence of personality and creativity on the performance of employees in Padang Panjang Regional Public Hospital with innovation as intervening variables - Helia, Suhelmi; Lismawati, Lismawati. R; Darwin, Darwin; Prastika, Anastatia (Jurnal Mantik, 2024)
This research aims to see the influence of Influence personality towards the innovation of Padang Panjang City Hospital employees. The influence of creativity on the innovation of Padang Panjang City Hospital employees. The influence of innovation on the performance of Padang Panjang City Hospital employees. The influence of personality on the performance of Padang Panjang City Hospital employees. The influence of creativity on the performance of Padang Panjang City Hospital employees. The influence of personality on the performance of Padang Panjang City Hospital employees with innovation as an intervening variable. The influence of creativity on the performance of Padang Panjang City Hospital employees with innovation as an intervening variable.The entire population and sample in this study Padang Panjang City Regional Hospital employs as many as 76 people. To determine the number of samples required, the technique of total sampling is used. The data analysis technique uses path analysis to meet the requirements of the classical assumption tests of normality, linearity, multicollinearity and heteroscedasticity. The results of this research show that personality and creativity significantly influence the innovation of Padang Panjang City Regional Hospital employees. Apart from that, personality, creativity, and innovation also significantly influence the performance of Padang Panjang City Hospital employees. The suggestions that can be put forward in this research are: so that the Padang Panjang City Regional Hospital can pay attention to the personality that occurs in employees at work, reduce the creativity that occurs and innovation must be the attention of employees because increased stress will trigger performance.